Analysis of social engineering prevention socialization patterns through websites and Twitter - Putri, Rahmadani Ningtyas Sekar; Hendi, Hendi Yogi Prabowo (Journal of Contemporary Accounting, 2024)
This study aimed to identify social engineering prevention socialization patterns through website and twitter by six major banks in Indonesia. This qualitative research utilized archival research method and documentary secondary data, namely using the bank's website and twitter media. This qualitative research uses content analysis and data was processed using NVivo 12 software. The results showed that the socialization of social engineering prevention provided by six banks in Indonesia through the website and twitter media contained information about the characteristics of social engineering, bank contact service facilities, and steps to prevent social engineering. Optimization of socialization through the website and twitter could be done by creating content that contains complete and up-to-date information about the characteristics of social engineering, contact service facilities, and preventive measures that could be visualized in the form of videos or attractively designed poster images.